One shot to control Pain: Decreasing postoperative opioid use in gynecologic oncology patients with intrathecal opioid injection - Yevgeniya Ioffe; Ruofan Yao; Eileen Hou; Michelle Wheeler; Mohamed Nour; Wei Yun Wang; Linda Hong (Elsevier, 2021)
Objectives: To determine whether regional anesthesia with single-shot intrathecal opioid injections (ITO) reduce postoperative pain and intravenous (IV) opioid use after exploratory laparotomy in major gynecologic surgeries. Methods: A retrospective chart review of 315 consecutive cases of patients who underwent an exploratory laparotomy on the gynecologic oncology service from July 2015 to January 2018 was conducted. Single-shot ITO was offered to all patients undergoing open abdominal surgery. The primary outcomes of interest were IV opioid use in morphine equivalents during the first 48 hours after surgery. Univariate analyses were performed to estimate the effect of ITO on IV opioid use at 0, 6, 12, 24 and 48 hours after surgery. Longitudinal regression analyses were performed to estimate the effect of ITO on changes in outcomes of interest over time, adjusting for potential confounders. Results: 35% (110/315) received ITO preoperatively. There were no differences in patient age, BMI, previous number of abdominal surgeries, history of opioid dependence, type of gynecologic surgery, or total EBL between the ITO and control groups. Preoperative ITO was associated with a significantly lower IV opioid requirement between 0 and 6 hours after surgery (9.7 ± 8.1 vs 14.3 ± 11.5, p < 0.0001) and between 6 and 12 hours after surgery (2.7 ± 3.8 vs 5.4 ± 9.5, p = 0.0054). There was no statistically significant difference in total hospital stay opioid requirement but median length of stay was increased by 1 day. Conclusions: Preoperative administration of ITO reduced IV opioid requirement in the first 12 hours postoperatively but was associated with median 1 day increase in hospital stay.